Development of Adoption Success Model Based on Electronic Regional Tax Returns - Dodik Ariyanto; Ayu Aryista Dewi; Henny Triyana Hasibuan (Indonesian Journal of Sustainability Accounting and Management, 2021)
The successful adoption of digital government services is critical. Even more so, in the era of the COVID-19 pandemic, e-government adoption needs attention from many sectors of society. During the pandemic, all government services have been increasingly provided through e-government. This paper examines the success of the electronic regional tax return (e-RTR), and the trust it has garnered as a significant factor in realizing a sustainable information society. The authors researched e-RTR users and data processing using partial least square regressions. The results demonstrated that trust in technology, information quality, information system quality, and service quality positively affected perceived usefulness and user satisfaction. However, trust in government itself has virtually no effect on perceived usefulness or user satisfaction. This indicates enhancing trust in the government should take precedence when the government uses e-government applications as a means of service to the community. Perceived usefulness and user satisfaction have a positive effect on net benefits, and net benefits positively affect the rise of a sustainable information society. This effect proves that a sustainable information society can be realized if the public perceives a net benefit when using e-government.